Investigations into nanofluids as direct solar radiation collectors. (1st May 2017) - Rose, B.A.J.; Singh, H.; Verma, N.; Tassou, S.; Suresh, S.; Anantharaman, N.; Mariotti, D.; Maguire, P.
Highlights: Different modelling approaches for the direct absorption of solar radiation by nanofluids discussed and evaluated. A wave optics model proposed for direct solar absorbing nanofluids. The wave optics model constructed and the results analysed. The optical properties of graphene oxide-ethylene glycol nanofluids characterised experimentally. The experimental results compared to those predicted by the model. Abstract: Nanofluids that directly absorb solar radiation have been proposed as an alternative to selectively coated metallic receivers in solar thermal collectors. Given the expense of characterising a potential nanofluid experimentally methods for comparing nanofluids virtually are needed. This paper develops a computational wave optics model using COMSOL to simulate the absorption of nanoparticles suspended in a fluid for solar radiation (380–800 nm) and compares it to experimental results using reflectance and transmission spectrometry. It was concluded that while both yielded data with matching trends, the exact absorption of some fluids differed by up to 1 AU. Optical characteristics of nanofluids comprising ethylene glycol (melting point −12.99 °C and boiling point range 195–198 °C at 1013 h Pa) and graphene oxide (sheets size 5 nm × 19 nm × 19 nm, volume fraction 0.004–0.016%) have been experimentally measured. An optimum volume fraction of 0.012% of graphene oxide has been identified achieving a minimum reflectance and highest absorbance over the visible spectral range.